2019
DOI: 10.3390/catal9080695
|View full text |Cite
|
Sign up to set email alerts
|

Influence of MoS2 on Activity and Stability of Carbon Nitride in Photocatalytic Hydrogen Production

Abstract: MoS2/C3N4 (MS-CN) composite photocatalysts have been synthesized by three different methods, i.e., in situ-photodeposition, sonochemical, and thermal decomposition. The crystal structure, optical properties, chemical composition, microstructure, and electron transfer properties were investigated by X-ray diffraction, UV-vis diffuse reflectance spectroyscopy, X-ray photoelectron spectroscopy, electron microscopy, photoluminescence, and in situ electron paramagnetic resonance spectroscopy. During photodeposition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…01-075-1539 in ICDD card). 33 Fig. 1b has eight characteristic peaks of the NFO NPs with planes of (111), (220), (311), (222), (400), (422), (511), and (440), respectively – ICDD card no.…”
Section: Resultsmentioning
confidence: 99%
“…01-075-1539 in ICDD card). 33 Fig. 1b has eight characteristic peaks of the NFO NPs with planes of (111), (220), (311), (222), (400), (422), (511), and (440), respectively – ICDD card no.…”
Section: Resultsmentioning
confidence: 99%
“…Apparently, efficient separation of photo‐generated electrons and holes occurs in MoS 2 @carbon. [ 30 ] Probably, incorporating MoS 2 in the carbon matrix, as well as the formation of C‐Mo bond facilitates the carrier transfer. We further monitored the CV curves evolution of MoS 2 @carbon during the switching of UV light.…”
Section: Resultsmentioning
confidence: 99%
“…Though many literatures have been reported the great potential of MoS 2 as HER electrocatalyst [3,21,22], the severe stacking of MoS 2 nanosheets during the preparation and electrochemical reaction process significantly impact its stability and hinders its application compared with Pt-based electrocatalysts [21,23]. Therefore, unless the electronic structure can be appropriately modulated by varying the chemical constituents [18] to increase the population of active sites [17] or introducing durable supportive materials [5,24] to prevent the aggregation, the 2D layered MoS 2 could hardly be employed into practical application without long-term stability [25].…”
Section: Introductionmentioning
confidence: 99%
“…Tungsten trioxide (WO 3 ) is another distinctive 2D layered oxide [26] with faster proton insertion kinetics than other two-dimensional transition metal chalcogenides, attributing to its larger proton diffusion coefficient [9]. Recently, improving the HER performance by designing and constructing various nanostructure components has been considered an available strategy to remarkably increase the active edge sites [25,27] and improve the long-term stability [28]. Indeed, researchers have reported that regulating the interlayer spacing of MoS 2 nanosheets by forming hetero-structure can optimize the HER performance [29][30][31].…”
Section: Introductionmentioning
confidence: 99%